RELEVANSI NILAI PENGUNGKAPAN MODAL INTELEKTUAL SECARA VOLUNTARY DAN INVOLUNTARY (THE VALUE RELEVANCE OF INTELLECTUAL CAPITAL VOLUNTARY AND INVOLUNTARY DISCLOSURES) - Rachmawati, Dyna; Susilawati, C. Erna (Jurnal Akuntansi dan Keuangan Indonesia, 2018)
The main purpose of this study is to examine the value relevance of intellectual capital dis-closures voluntary and involuntary. Previous studies use annual reports as main source to determine intellectual capital disclosures voluntary. Annual report is less reliable, unobjective and contain advertorial. This study seeks for alternative sources to identify intellectual capital disclosures. To determine intellectual capital disclosures voluntary (involuntary), we use website (online business media). This study uses companies in Kompas 100 during January – December 2017 as research samples. Intellectual capital disclosures measured by content analysis method. The results show that intellectual capital disclosures both voluntary and involuntary have value relevance. The main contribution of this study is an alternative source to collect data on intellectual capital disclosures.